Processo ensino-aprendizagem do aluno na EAD e o mundo do trabalho: possibilidades e limites - Afonso, Luiz Eduardo de Barros (2023)
E-learning has been much discussed in academia and further studies are needed to broaden the debate. Thus, the present study investigates possibilities and limits found in the teaching of e-learning by the working student for the development of emancipatory conditions of human life. The objective is to promote subsidies for a training process in e-learning aimed at working students that go beyond forms of domination and oppression. Based on the theoretical framework of Antunes (2009, 2018), Giroux (1997) and Freire (2019), we analyzed data collected through a questionnaire and interviews prepared from the axes: class consciousness, work x quality of life, working conditions and human formation. The subjects of the research are students and alumni of undergraduate distance learning courses at the Distance Higher Education Center of the State of Rio de Janeiro (Cederj). The results found show that there are more limits than possibilities for distance learning students to develop emancipatory conditions for human life. There are limits that compromise this learning: the mutations that result from crises in the capitalist system, affecting the spectrum of the world of work; the loss of working class rights; the quality of life that is impacted by financial health and that also impacts physical and mental health; the “flexibility” of the world of work; the conscience in relation to the class and the very “flexibility” of the adopted methodology. Possibilities are: the dialogues raised about public policies, teaching, access and permanence in higher education in e-learning, work as a free activity; of health and food policies and the restructuring of the methodology adopted by the Cederj Consortium